Pengaruh Sistem Informasi Akuntansi dan Pelaporan Keuangan terhadap Pengendalian Manajemen pada Perusahaan Jasa Konstruksi (PT. X) di Jakarta - Edison Hamid (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2018)
Accounting information system in charge of providing the information needed to facilitate monitoring and assessment of control measures against the management. There are five main functions of the accounting information system of data collection, data processing, data management, control data (including security), and producer information. This study aims to examine the effect of accounting information systems and financial reporting to management control. The results are expected to provide benefits in explaining and predicting the effects of accounting information systems and financial reporting to management control. This form of survey research studies that used questionnaires to collect data that need. To provide an overview of the demographics of respondents, the research data were analyzed with descriptive statistics. The quality of data generated from the use of research instruments was evaluated by rehabilitation and validity testing. The hypothesis was tested by multiple regression analysts to determine its influence on management control. The results with the conclusion that the accounting information system significantly influence the management control, financial reporting significant influence on management control, and test results together financial reporting was only significantly affected majanemen control, whereas no effect of accounting information systems are significant.